Dvoje vstopov v slovensko zgodovino - Maver, Aleš (Studia Historica Slovenica, 2024)
The paper examines the relationship between two possible entries into Slovenian history and the dynamics of the relationship between them in the 20th century. The focus is on the role of the "south-eastern current". The current relationship between these two possible entries into Slovenian history has undoubtedly been significantly (co)determined by the unfolding of three major Slovenian turning points in the 20th century, after the First and Second World Wars and after 1989, respectively. At the same time, the very suddenness and thoroughness of the Slovenian turn to the South-East after the First World War did not mean that there were no preconditions for it in the earlier period. One of the essential entry points for it was, at least in our view, the embarrassment about the origins of Christianity in the historical Slovenian areas. In addition, it is important to point out a fundamental uncertainty that has accompanied the quest for the and for the (greater) political independence of Slovenes since the formulation of the programme for a united Slovenia and in spite of it.
Keywords: Central Europe; južnoslovansko povezovanje; prelomi 20. st.; Slovenian history; slovenska zgodovina; South Slavic integration; Srednja Evropa; upheavals of the 20th cent.